Implementation of Project CBISp-EDP (Communicate, Build and Intensify Stakeholders’ Participation- Exemplified and Deepened Partnership) and External Stakeholders’ Participation - Cincy Merly Gecolea; Elsa D Pagulayan; Peejay G Gecolea (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
The study mainly focused on assessing the implementation of Project CBISp-EDP and external stakeholders’ participation in Calamba Bayside Integrated School. The study utilized a descriptive correlational research design. The respondents of the study were the 80 teachers and 99 parents of CBIS. Teacher-respondents were identified using a simple random sampling technique, while purposive sampling was used to identify the parent-respondents. Results of the study revealed that all teachers have the same level of observation in implementing Project CBISp-EDP. It also showed that external stakeholders participated in most school-initiated activities. Moreover, it also disclosed that the implementation of Project CBISp-EDP has a significant relationship with external stakeholders’ participation. It is recommended that the school consider the crafted action plan to strengthen stakeholders’ participation further.